1980
DOI: 10.1084/jem.151.3.773
|View full text |Cite
|
Sign up to set email alerts
|

Separate cytotoxic T lymphocyte subsets recognize the different H-2 specificities.

Abstract: Using a monolayer adsorption technique, the fine specificity of cytotoxic effector T lymphocytes (CTL) generated against allogeneic or semi-allogeneic H-2 haplotypes was investigated. The results show that: (a) CTL reacting with the private specificity expressed on an H-2.K molecule can be separated from those reacting with the public specificities expressed on the same molecule and (b) the CTL that recognize cross-reacting H-2 determinants (public specificities) can also be separated into several subpopulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1980
1980
1984
1984

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…3D and E) confirmed this hypothesis, thus demonstrating that the CTL clones that mediated lysis against TNP-self targets were not responsible for the lysis of FITC-self targets. Thus, alloantigen-activated CTL cultures appear to be composed of multiple cytotoxic components (13,14) of which specific subpopulations are able to recognize different self plus haptenated target cells. These findings, therefore, demonstrate that this response is immunologically specific, and is not a result of an artifact induced by hapten conjugation to the target cells.…”
Section: Discussionmentioning
confidence: 99%
“…3D and E) confirmed this hypothesis, thus demonstrating that the CTL clones that mediated lysis against TNP-self targets were not responsible for the lysis of FITC-self targets. Thus, alloantigen-activated CTL cultures appear to be composed of multiple cytotoxic components (13,14) of which specific subpopulations are able to recognize different self plus haptenated target cells. These findings, therefore, demonstrate that this response is immunologically specific, and is not a result of an artifact induced by hapten conjugation to the target cells.…”
Section: Discussionmentioning
confidence: 99%
“…The CR CTL reflect the peculiarities of their specificity and can be revealed not only in the crude CTL populations but in a part of their clones (Taswell et al 1980, Guimezanes et al 1982, Plata 1982, as well as in cloned CTL precursors (Teh et al 1978). The absorptions of monospecific CTL have shown that they consist of subpopulations capable of adhering to the particular CR TC in a selective fashion (Andreev et al 1976, Geib et al 1978, Vasquez et al 1980). To study the nature of this phenomenon, the fine specificities of the CR CTL fractions isolated from the given "irrelevant" mon-olayers bearing mutant (Brondz et al 1979b) or allogeneic haplotypK {Brondz et al 1982b, c) were estimated.…”
Section: Narrow Receptor Specificity and The Clonal Structure Of The mentioning
confidence: 99%